Intertextual references as a manifestation of advertising creativity on the example of the Lidl chain of stores - Banach, Agnieszka (Linguistic creativity in marketing, 2022)
The article focuses on the linguistic analysis of intertextual references appearing in the advertisements of the Lidl store network posted on the Facebook social network. The published content is arranged in a triadic pattern of intertextuality - ludic function - marketing function. Only references to literature, film and the music scene in general were analysed. The advertising slogans fully exhaust the features of linguistic creativity, initialize intelligent and humorous game with the recipient. In addition, the references used are focused around popular culture texts, and at the same time the slogans implement the assumptions of the genre, such as: brevity, attractiveness, persuasiveness, ease of remembering.